6y-9-2y+4=0

Simple and best practice solution for 6y-9-2y+4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-9-2y+4=0 equation:


Simplifying
6y + -9 + -2y + 4 = 0

Reorder the terms:
-9 + 4 + 6y + -2y = 0

Combine like terms: -9 + 4 = -5
-5 + 6y + -2y = 0

Combine like terms: 6y + -2y = 4y
-5 + 4y = 0

Solving
-5 + 4y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 4y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 4y = 0 + 5
4y = 0 + 5

Combine like terms: 0 + 5 = 5
4y = 5

Divide each side by '4'.
y = 1.25

Simplifying
y = 1.25

See similar equations:

| 3+2j=7 | | 3xy-14=12z | | 3n-7=6 | | 10x+2+68+70=180 | | x-10.16=-12 | | -8y-4=2y+16 | | 8x-5x-11=52 | | 5(x+1)-4x=6-2x-(4-2x) | | (x+5)(x-8)(4x-5)=0 | | x+4.8=-7.7 | | 5z=7y+2xy-3 | | 3u-4=5 | | R-2+R+7= | | -28+x=2.6 | | 8y+11=12y+7x | | -3=18m+6n | | 1x+11+2x-5=90 | | sqrt(7x-7)-9=3x-20 | | 43.01*0.84= | | -345=-7(7-6n)-5n | | s(t)=16t^2+4t+7 | | x+87+50+50=180 | | 10m+50=7m+80 | | 3-(x+2)=7 | | 43.4-0.39*0.84= | | (d^4+3d^3-6d^2-28D)y=0 | | y=10-5*-2 | | (-3x)+y=0 | | s(t)=-16t^2+4t+7 | | -4(1+7m)=-200 | | 2n+1=4 | | (d^3+2d^2+d+2)y=0 |

Equations solver categories